In Vitro Susceptibility of Nocardia asteroides to N-Formimidoyl Thienamycin and Several Cephalosporins - Cynamon, Michael H. (1981)
The susceptibility of N. asteroides to N-formimidoyl thienamycin, cefamandole, cefoxitin, and moxalactam was determined by agar dilution. N-Formimidoyl thienamycin was the most active, inhibiting eight of nine strains at 1.56 μg/ml.